A THEORITICAL STUDY OF BENZYL BENZOATES WITH AGARICUS BISPORUS TYROSINASE INHIBITORY PROPERTIES.: Pharmaceutical Science-Pharmaceutical Chemistry - TIGULLA, PARTHASARATHY; KANCHANAPALLY, RAVINDRA CHARY; MACHA, RAMESH; VUNGUTURI, SHANTHI (International Journal of Life Science and Pharma Research, 2011)
Tyrosinase is a copper containing multifunctional oxidase that catalyzes both the hydroxylation of mono phenols to diphenols and the oxidation of o-diphenols to o-quinones. Tyrosinase is involved in neuromelanin formation in human brain and contribute to neurodegeneration associated with parkinson’s disease. The benzyl benzoate analogs were found to inhibit tyrosinase enzyme. The biological activity of these analogs were correlated to different molecular properties. The AM1and PM3 semiempirical methods were used to estimate vertical ionization potentials(IPv’s), electron affinity (EA) , electronegativity (χ), hardness (η), softness (S), electrophilic index (ω), partition coefficient (LogP),hydration energy(HE), ionization potential(IP) and charges. The different modeled equations were proposed by regression analysis. The leave-one-out cross-validation method was used to estimate the predictive power of final QSAR equations. The hydration energy (HE) and ionization potential (IP) were found to be indicative molecular properties by regression analysis. The high inhibitory nature of these analogs is found to have lower values of HE and IP. The lower values of HE and IP are responsible for binding ring A and ring B to the bi copper centre of tyrosinase. The inhibitory effect of benzyl benzoate analogs mainly depends on the position of the hydroxyl moieties instead of their quantity.